Statistical assessment of stability and compatibility of protease extracted from thermo tolerant Bacillus licheniformis BWU-1 - D.U. Bhusare2, P.S. Wakte1 and (Current Botany, 2011)
<span style="font-size: 8pt; font-family: Byington; mso-fareast-font-family: 'Times New Roman'; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Proteolytic enzymes particularly proteases, have become an important and essential part of the industrial processes including pharmaceuticals, food products and laundry detergents. <span style="font-size: 8pt; font-family: Byington; mso-fareast-font-family: 'Times New Roman'; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: HI;">The studied physico-chemical parameters revealed that the optimum pH and temperature was 10 and at 50°C. <span style="font-size: 8pt; font-family: Byington; mso-fareast-font-family: 'Times New Roman'; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Detergents such as Ariel, Tide, Rin, Ghadi, Surf excel, Nirma and Sassa possesses Proteolytic enzymes, mostly extracted by members belongs from the genus Bacillus. Present investigation, describes the compatibility of protease produced by the thermotolerant Bacillus licheniformis BWU-1 with commercial laundry detergents. Stability studies indicated that this enzyme retained about 178% and 143% of its maximum activity after 6 h at 45°C in presence of CaCO3 and MgSO4 respectively. A stronger inhibitory effect was observed in presence of FeSO4 and HgCl2 resulted in loss of enzyme activity. A lesser amount of inhibitory effect was observed at 1-2% triton X-100, 0.1-0.2 % SDS, 1-2% H2O2 and 1-4% EDTA all they showed significant p-value (<0.05) while remaining all the concentrations were inhibited the enzyme activity. After supplementation of Ca+2, the protease retained more than 90 and 100 % of its activity after 1 h incubation at 50°C in presence of Rin and Surf excel respectively.